2021
DOI: 10.1080/21655979.2021.1981798
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circPRKDC promotes tumorigenesis of gastric cancer via modulating insulin receptor substrate 2 (IRS2) and mediating microRNA-493-5p

Abstract: CircPRKDC has been disclosed to participate in the tumorigenesis of serval tumors, but the regulatory mechanisms of circPRKDC in GC are still unknown. CircPRKDC, miR-493-5p, and insulin receptor substrate 2 (IRS2) levels were tested by RT-qPCR. The epithelial-mesenchymal transition (EMT)-related protein levels were evaluated via western blot. The cell viability, migration and invasion were evaluated through CCK-8 and Transwell assays. Luciferase reporter and RIP assays were employed to confirm the binding abil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The tissue expression profile analysis showed that the expression of bbu-miR-493-5p was significantly higher in buffalo skeletal muscle than in other organs = (heart, liver, spleen, lung), suggesting that it plays an important role in buffalo skeletal muscle development and is worth researching. miR-493-5p has been widely used as a tumor suppressor in various cancers, such as hepatocellular carcinoma [20,21], cervical cancer [22], renal cell carcinoma [23], gastric cancer [24], and so on. In recent years, miR-493-5p has also been found to be associated with skeletal muscle growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…The tissue expression profile analysis showed that the expression of bbu-miR-493-5p was significantly higher in buffalo skeletal muscle than in other organs = (heart, liver, spleen, lung), suggesting that it plays an important role in buffalo skeletal muscle development and is worth researching. miR-493-5p has been widely used as a tumor suppressor in various cancers, such as hepatocellular carcinoma [20,21], cervical cancer [22], renal cell carcinoma [23], gastric cancer [24], and so on. In recent years, miR-493-5p has also been found to be associated with skeletal muscle growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that miR‐493‐5p has antitumor functions in various cancer types. Although miR‐493‐5p has been reported to function in a suppressive manner in various cancer types, 27 , 28 , 29 it has not been reported in cholangiocarcinomas, including ICC. The expression patterns and biological mechanisms of miR‐493‐5p in ICC progression have not yet been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the expression and function of the IRS may vary in the different types of cancer. For example, IRS-1 has been associated with proliferation, growth, and anti-apoptosis, whereas IRS-2 has been linked to metastasis, motility, and invasion [ 22 , 23 , 24 , 25 , 26 ]. IRS proteins participate in canonical pathways, the phosphorylation of which is induced by the insulin receptor.…”
Section: Introductionmentioning
confidence: 99%